2013
DOI: 10.1152/japplphysiol.00466.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and autonomic responses to physiological stressors before and after six hours of water immersion

Abstract: The physiological responses to water immersion (WI) are known; however, the responses to stress following WI are poorly characterized. Ten healthy men were exposed to three physiological stressors before and after a 6-h resting WI (32-33°C): 1) a 2-min cold pressor test, 2) a static handgrip test to fatigue at 40% of maximum strength followed by postexercise muscle ischemia in the exercising forearm, and 3) a 15-min 70° head-up-tilt (HUT) test. Heart rate (HR), systolic and diastolic blood pressure (SBP and DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 64 publications
(97 reference statements)
6
59
1
Order By: Relevance
“…A recent study has shown that both decreased SNA and increased para-SNA followed 6 h in-water immersion when PV was significantly reduced (117). By contrast, they reported that aldosterone, ANP, AVP, and NE were unchanged postimmersion.…”
Section: Egress From Water Immersionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study has shown that both decreased SNA and increased para-SNA followed 6 h in-water immersion when PV was significantly reduced (117). By contrast, they reported that aldosterone, ANP, AVP, and NE were unchanged postimmersion.…”
Section: Egress From Water Immersionmentioning
confidence: 96%
“…By contrast, they reported that aldosterone, ANP, AVP, and NE were unchanged postimmersion. Importantly, they also showed that cardiovascular and autonomic control are not sufficient to prevent orthostatic intolerance postimmersion (117).…”
Section: Egress From Water Immersionmentioning
confidence: 99%
“…; Florian et al. ). During WI, central blood volume increases due to fluid shifts from the intracellular and interstitial fluid compartments to extracellular compartment (Epstein ) and redistribution of blood volume from the lower extremities to the thorax (Greenleaf et al.…”
Section: Introductionmentioning
confidence: 98%
“…; Tripathi ; Florian et al. ), together with augmented excretion of fluid and electrolytes (Norsk et al. ; Epstein ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation